Analysis of Fatigue Life of Tugboat Towing Hook Construction Using Finite Element Method - Adnyani, Luh Putri; Arsyad, Muhammad Abid Mapariorio; Nurcholik, Samsu Dlukha (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2020)
The towing hook on the tugboat has a function to pull the barge. Because of this ability, a good towing hook construction is needed to work optimally. Indications for the good construction is the value of fatigue life, which is more than the value of design life of 20 years. A towing hook detail on tugboat from PT. Asia Aditama Shipyard – Balikpapan was selected as an example. This study aims to obtain the value of fatigue life based on the total resistance calculated by BHP data in full, 75%, and 50% of the total displacement volume and estimate the maximum size of a barge, based on maximal towing pull capacity. The benefits of this research are providing information about the fatigue life of a towing hook, analyzing several possible load cases, and giving the recommendation of the maximum principal dimensions of the barge that the towing hook can be pulled. The method used in this study is the finite element method using ANSYS, the fatigue life calculation approach is the Palmgren–Miner cumulative damage method and refers to the DNVGL rule. The results of the calculation of fatigue life in the maximum towing pull condition are 22 years, 22 years, and 23 years at 100%, 75%, and 50%, respectively. The main size of barges that can be towed by Tugboats under maximum towing pull conditions are LOA = 147m, LWL = 144,529m, B = 35m, H = 13m, T = 11m.